Assessment of the Impact of COVID-19 on Sustainable Forest Management in West Africa: cases of Benin, Côte d’Ivoire and Ghana - (:unkn) unknown (My University, 2023)
Evidences on how COVID-19 has impacted the forestry sector in West Africa and at country level are lacking. In this regard, this study was conducted to assess the impact of the pandemic on: (i) sustainable forest management in West Africa, (ii) forest-dependent people, and local communities, (iii) forest industry and international cooperation. A mixed-methods approach, involving a literature review based on desk review of existing published studies, reports, and policy briefs, and key informant interviews was used. The results revealed that the protective measures against COVID-19 have resulted in the postponement, and in some cases outright cancellation, of forest management activities with the increase in illegal activities such as wildlife poaching, gold panning, and logging; among the local communities, women and young people were the most affected by the pandemic with increase in the dependence on some forest goods and services; supply chains were adversely affected impacting on exports of timber and imports of forest products. Monitoring of the resource was a problem during the pandemic; there is therefore a need to explore or incentivize community monitoring, in particular using IT and mobile technologies, to reduce dependency on physical monitoring by governmental agents. Improvements in the forest law enforcement and governance systems should be considered by the forest authorities to combat illegal activities in the forests. West African governments and private-sector businesses should recognize the need for international market diversification to reduce dependence on one specific market. This could be done by developing, promoting, and expanding local and regional market destinations for forest products.
Keywords: African Research